2D LC as a tool for standardization of Foenugraeci semen extracts containing compounds with anti-Helicobacter pylori activity. Issue 6 (4th March 2021) - Król-Kogus, Barbara; Głód, Daniel; Hałasa, Rafał; Krauze-Baranowska, Mirosława; Pobłocka-Olech, Loretta
Abstract : An on-line LC-LC-DAD-ESI-MS method was established for quantitation of C-glycosylflavones in fenugreek seeds. Anti- Helicobacter pylori activity of standardized 70% methanol extract from fenugreek seeds and vitexin has been demonstrated. Abstract : The on-line heart-cutting two-dimensional liquid chromatography method with the use of a diode array detector and a mass spectrometer (LC-LC-DAD-ESI-MS) was established and validated for quantitation of C-glycosylflavones in fenugreek seeds ( Foenugraeci semen, Trigonella foenum-graecum L.). The first- ( 1 D) and second- ( 2 D) dimensional separations were performed on Kinetex C-18 columns with different diameters, respectively, and gradient ( 1 D) and isocratic elution ( 2 D). Finally, 17 compounds were separated, 13 of which were quantified by 1 D separation and 4 compounds by 2 D separation. As a result, it was pointed out that fenugreek seeds of Polish origin can be considered as a rich source of C-glycosylflavones. Antibacterial activity against Helicobacter pylori of standardized 70% methanol extract from fenugreek seeds has been demonstrated, in contrast to the inactive aqueous extract. Anti- H. pylori activity of the 70% methanol extract can be related to a higher concentration of C-glycosylflavones. This is the first report on the bactericidal activity of vitexin, diosgenin, tigogenin and sarsasapogenin against H. pylori and the bacteriostatic activity of orientin against this bacterium.